Transitions between informal and formal employment: Results from a worker survey in Bangladesh - Italo A. Gutierrez; Krishna B. Kumar; Minhaj Uddin Mahmud; Farzana Munshi; Shanthi Nataraj (IZA Journal of Development and Migration, 2019)
We study transitions between different types of formal and informal employment using retrospective job histories from a new survey in Bangladesh. Workers transitioning between jobs are most likely to remain in the same type of employment, although there is still substantial churn across employment types. Private wage employees have higher probability of transitioning to a new job, and changes in earnings and benefits suggest evidence of upward mobility. Nevertheless, there is also non-trivial risk of downward mobility, especially for those transitioning into casual employment, which has the lowest level of earnings and benefits and the highest levels of exposure to workplace hazards and violence. Overall, the informal sector appears to include subpopulations consistent with both the traditional view that it is a segmented portion of the labor market with few prospects of upward mobility, and with the alternative view that it is a dynamic, entrepreneurial alternative to wage employment.
Keywords: J32; J46; J62; 330; Informal labor; Self-employment; Casual workers; Job transitions; Working conditions; Job benefits